Responsabilidade social na Universidade Federal da Fronteira Sul – uma análise histórica - Eidt, Elise Cristina (2019)
The University Social Responsibility (USR) has been increasing over the past few years, and it is directly related to the discussion about redefining roles and the scope of activities of Higher Education Institutions (HEI), with regard to the ethical and transparent management of administrative, educational, cognitive and social processes. Despite the awareness about the USR practice, there is still a scenario of low disclosure, lack of support, incentive and recognition of the actions, in addition to the few empirical studies which analyze the internal and external perception of the public, mainly in public HEI. The general objective of the present study was “To diagnose the management of University Social Responsibility (USR) at Federal University of Fronteira Sul (UFFS)”. Initially, a historical description of Social Responsibility (SR) has been made, followed by an analysis of the trajectory of the university and its constituent tripod, the detailing of the USR approach, with bibliometric study and integrative review of international literature, and lastly, the presentation of a theoretical model of USR adapted to the research, according to what Vallaeys, Cruz and Sasia (2009) proposed. The research methodology was characterized by the historical dimension of the USR phenomenon, using qualitative and quantitative approaches, application of interviews, questionnaires, focus group and analysis of institutional documents. The research involved 218 participants (eight managers, six representatives of the regional community, 113 students, 65 professors, and six administrative technicians in education) with whom the following axes of the USR theoretical model were evaluated: Responsible campus, Professional qualification and citizen training, Social knowledge management and Social participation. Through the analysis of documents and the institutional history it was found that the conception which bases the practice of the USR at UFFS is directly related to the characteristics of the context in which it is situated. A constructive direction was also observed in the teaching actions, research and extension with the axes of the USR, but improvement is necessary to materialize more dimensions of the thematic, especially those related to the axis Responsible campus. In general, the perceptions of the internal and external public were consistent with the four researched axes, and it is recognized that the community is aware of the meaning of a social responsible university, but it also indicates opportunities for improvement and future challenges from which prepositions of actions are presented. Therefore, it is estimated that the UFFS is aware of the importance and tends to promote the USR, for its scenario is directly related to its constitution and principles, but the actions still do not reflect an integral and transversal Social Responsibility management model. Lastly, the institutionalization of a Social Responsibility Committee and the structuration of an RSU policy are proposed, what would allow the permanent monitoring of this important topic for the HEI, in order to legitimize the practices which build the true social mission of higher education.